Diversity and zoogeography of mammals at the Levantine Land Bridge, Jordan - MOHAMMAD A. ABU BAKER; ZUHAIR S. AMR (Society for Indonesian Biodiversity, 2026)
Abstract. Abu Baker MA, Amr ZS. 2026. Diversity and zoogeography of mammals at the Levantine Land Bridge, Jordan. Biodiversitas 27 (7): d270709. https://doi.org/10.13057/biodiv/d270709. Jordan hosts a remarkably diverse mammalian fauna owing to its position at the intersection of three major zoogeographic realms (Afrotropical, Oriental, and Palaearctic) within the Levantine Land Bridge. This study aims to synthesize current knowledge of mammalian diversity in Jordan and interpret its biogeographic patterns in relation to habitat heterogeneity and historical processes. The analysis is based on published records, faunal surveys, and historical accounts documenting species occurrence across the country. A total of 83 mammalian species representing 8 orders have been recorded in Jordan, reflecting both wide-ranging taxa and habitat-restricted specialists. Zoogeographically, 46.84% of species are of Palaearctic origin, 31.65% Saharo-Sindian, 16.46% Afrotropical, and 7.59% Oriental. Approximately 39.24% of species are habitat-restricted, while 39.24% occur at the edges of their global distribution ranges. Species distributions correspond strongly to ecological gradients: forest-associated taxa, such as wood mice, stone marten, and several horseshoe bats, are largely confined to Mediterranean woodland habitats; Psammophilous gerbils occupy isolated sand dune systems within desert landscapes; and saxicolous species, including spiny mice, rock hyrax, Blanford's fox, and Nubian ibex, are restricted to rocky terrains. Jordan represents a critical biogeographic boundary, marking the northern or southern limits of several taxa. Afrotropical species extend northward along the Rift Valley, Palaearctic species reach their southern distribution in the Mediterranean highlands, and Oriental elements occur more locally. In addition, past geological and climatic events have resulted in the persistence of relic populations, such as dormice in southern and eastern rocky deserts and a geographically isolated melanistic population of spiny mice in the eastern basalt desert. This unique convergence of faunal elements and habitat-specific assemblages highlights the conservation importance of Jordan's ecosystems. Protecting habitat diversity and geographically isolated populations is essential for maintaining the country's role as a biogeographic transition zone and for preserving species at the limits of their global distributions.